Documents relating to research for articles by Florence O’Donoghue, with enclosures on ambushes during the War of Independence at Crossbarry, Kilmichael, Upton, etc. - O'Donoghue, Florence, 1895-1967; Murray, Patrick A.; Deasy, Liam, 1896-1974; Neenan, Cornelius F., 1894-1979 (1951)
Includes copy documents, statements by those involved in ambushes and responses to draft articles by O'Donoghue.
Some items inscribed on reverse of other documents.
Keywords: Barry, Tom, -- 1897-1980; Deasy, Liam, -- 1896-1974; Irish Republican Army. -- Southern Command, 1st; Ireland -- History -- War of Independence, 1919-1921; Ireland -- History -- 1910-1921